Implementing tasks that stimulate critical thinking in EFL classrooms - Fúquen Martínez, Aida Yolima; Jiménez Niño, Patricia Kim (Universidad Pedagógica y Tecnológica de Colombia, 2013)
This article of reflection introduces the insights drawn from a didactic activity implemented in two EFL classrooms at the Uptc (Universidad Pedagógica y Tecnológica de Colombia) in Tunja, by twoteachers belonging to the IIDI (Instituto Internacional de Idiomas). The activity was carried out with the objective to arise awareness about the need to strengten the critical thinking skill in undergraduate students through music and, by using the English language. The article aims to invite teachers to use this type of tasks stimulating reflection, problem-posing, and problem solving regarding social concerns. The findings state that the implementation of Critical Thinking relatedtasks can indeed become an effective strategy to foster criticality. The paper begins with the rationale. Afterwards, it presents the theoretical framework supporting the proposal, and shows the findings. Finally, the article ends with the conclusions, the appendix, and the references.